1984
DOI: 10.1002/aja.1001710107
|View full text |Cite
|
Sign up to set email alerts
|

Development of the vascular bed in the rabbit ear: Scanning electron microscopy of vascular corrosion casts

Abstract: The development of the vascular bed in the rabbit ear was investigated using vascular corrosion casts from animals of various ages. Examination of the casts revealed that the arrangement of the major auricular arteries and veins was determined before birth and was maintained during postnatal growth of the ear. Furthermore, the number of arteries branching off the central ear artery and the lateral arteries did not increase with increasing ear length. Scanning electron microscopic examination of lateral segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…The injection site on each ear was shaved and applied with lidocaine cream and cleaned with a saline gauze 30 min later. The ventral side of the rabbit ear was then irradiated with a strong light, and a filler was injected into the main trunk of the central ear artery (CEA) with a 27-G needle (0.5 mm) from 1 cm above the medial ramus of the central ear vein (CEV), which is about 4–5 cm from the root of the rabbit ear [8] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The injection site on each ear was shaved and applied with lidocaine cream and cleaned with a saline gauze 30 min later. The ventral side of the rabbit ear was then irradiated with a strong light, and a filler was injected into the main trunk of the central ear artery (CEA) with a 27-G needle (0.5 mm) from 1 cm above the medial ramus of the central ear vein (CEV), which is about 4–5 cm from the root of the rabbit ear [8] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Although it is stated that increased blood flow is the main detenninant of formation and maintenance of AVAs in the adult rabbit ear during wound healing (Clark, 1934b;Rosatti, 1956), it is not possible that the increase in blood pressure occurring during development of the rabbit (Mott, 1965) is directly related to the increase in the AVA number because it has been reported that blood pressure reaches its highest point in rabbits approximately in 8 weeks while the AVA number continues to increase until the ears reach their maximum length in rabbits approximately in 16 weeks. For this reason, it has also been stated that metabolic factors should be taken into consideration to maintain AVA density (Morris, 1984). It has been reported that the density of AVA in chics increases noticeably during the posthatching period and that the number of cell layers in the AVA wall amounts to 4-5 in chicken of 5 months, whereas it is 2 in the newly-hatching chics (Midtgard, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AVA development relating to human nasal mucosa (Rosatti, 1954) and human ear (Prichard, 1956) was studied. This development was also studied in the ears of rabbits (Clark, 1934b;Morris, 1984;1986), the skins of chicken (MidtgArd, 1989) and the tongues of kittens (Jasinsky, 1979). However, no AVAs were noted in rabbits under 8 day (Morris, 1984) and in 4-day kittens (Jasinsky, 1979).…”
mentioning
confidence: 99%
“…The central auricular branch (also named central ear artery) and the rostral auricular branch form the major source of blood supply to the rabbit ear [25]. The upper close-up photograph of the rabbit ear vascular anatomy shows small branches from the central auricular branch.…”
Section: Rabbit Ear Vasculaturementioning
confidence: 99%